Comparison of common green bottle flies (Lucilia sericata Meigen) and stingless bees (Tetragonula laeviceps Smith) as pollinating agents for imported true shallot (Allium cepa L.) seed production - Putra, Ramadhani Eka; Sulistia, Winda Nazirah; Kinasih, Ida; Raffiudin, Rika; Purnobasuki, Hery; Soesilohadi, RC Hidayat; Fajrina, Nur; Juansa, Andrina (Agriculture and Natural Resources, 2022)
Importance of the work: The pollination process for true shallot seeds (TSSs) is usually conducted based on high-cost hand pollination that could be replaced by insects. Objectives: To investigate two insect species as possible replacements to hand pollination for TSS production. Materials & Methods: Common green bottle flies (Lucilia sericata Meigen) and stingless bees (Tetragonula laeviceps Smith) were used as pollinating agents for shallot plants in cages. The applications consisted of 100 flies, 300 flies, 500 flies, 1 colony of stingless bees, hand pollination, open pollination and a control. Variables observed were insect activity, pollination success and seed quality. Results: Green bottle flies visited more flowers (15.2 ± 4.5 flowers/min) and spent, significantly, more time on flowers (135 ± 46 s/flower) than stingless bees (5 ± 3 flowers/min and 81 ± 18 s/flower, respectively). The highest pollination success and seed quality values were recorded for the hand pollination group (61.91% and 1.22 g, respectively) though these were not significantly different from the results using 500 green bottle flies (60.56% and 1.09 g, respectively). However, the seeds produced using stingless bee pollination had a significantly higher germination rate. Main finding: Green bottle flies and stingless bees could be applied (partially or totally) as a replacement for hand pollination for imported TSS production. However, due to the possible negative consequences of the mass production of green bottle flies, the application of stingless bees as pollinating agents for TSS production would be preferable.